MAQAM CINTA DALAM PANDANGAN AL GHAZALY - Rauf, Rusmin Abdul (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
This article will discuss the concept of love conveyed by Imam Al Ghazali. Imam al Ghazali is one of the most influential Muslim thinkers. In the concept of happiness, he emphasizes the importance of love in achieving happiness. In fact, he said that the essence of Islam is love for Allah SWT. This study found that al Ghazali divided love into several parts of it, love for oneself, for good people, and even about love which is a microcosm of compatibility with the human soul. In this case, al Ghazali has provided various arguments to strengthen his thesis. In addition, he has also explained things that strengthen love and signs of people who love Allah.